1989
DOI: 10.1172/jci113948
|View full text |Cite
|
Sign up to set email alerts
|

Stretch-induced atriopeptin secretion in the isolated rat myocyte and its negative modulation by calcium.

Abstract: Cellular mechanism(s) regulating atriopeptin secretion and processing by the atrial myocyte are currently unknown. Osmotic stretch of isolated atrial myocytes as well as potassium chloride depolarization were potent stimuli of atriopeptin secretion. Release was potentiated by buffering either extracellular calcium with EGTA or intracellular calcium with the intracellular chelator, BAPTA AM. Atrial release of atriopeptin was inhibited after administration of ionomycin which elevates intracellular calcium. Fetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…Secondly, we demonstrated that 46 nm TPA, known at these concentrations (10-100nM) to activate protein kinase C in this experimental model (Yuan et al, 1987), caused a slowly developing increase in the IR-ANP release from ventricular tissue. A similar pattern of ANP release with respect to levels and time course has been observed before, when intact rat hearts (without atrialectomy) were perfused under these experimental conditions (Ruskoaho et al, 1985; Greenwald et al (1989) reported that KCl produced a dosedependent release of ANP from suspensions of neonatal rat ventricular cells in culture and suggested that, like the atrial myocyte, the ventricular myocyte possesses the cellular mechanism(s) necessary to secrete ANP by a regulated pathway. In contrast, Bloch et al (1988) reported that shortterm exposure to the Na+-K+-adenosine-triphosphatase inhibitor, ouabain, stimulates the secretion of IR-ANP from atrial, but not from ventricular, cardiomyocytes in culture.…”
Section: Discussionsupporting
confidence: 78%
“…Secondly, we demonstrated that 46 nm TPA, known at these concentrations (10-100nM) to activate protein kinase C in this experimental model (Yuan et al, 1987), caused a slowly developing increase in the IR-ANP release from ventricular tissue. A similar pattern of ANP release with respect to levels and time course has been observed before, when intact rat hearts (without atrialectomy) were perfused under these experimental conditions (Ruskoaho et al, 1985; Greenwald et al (1989) reported that KCl produced a dosedependent release of ANP from suspensions of neonatal rat ventricular cells in culture and suggested that, like the atrial myocyte, the ventricular myocyte possesses the cellular mechanism(s) necessary to secrete ANP by a regulated pathway. In contrast, Bloch et al (1988) reported that shortterm exposure to the Na+-K+-adenosine-triphosphatase inhibitor, ouabain, stimulates the secretion of IR-ANP from atrial, but not from ventricular, cardiomyocytes in culture.…”
Section: Discussionsupporting
confidence: 78%
“…3 A and B); furthermore, AP-126 is only 50% cross-reactive with AP-28 with this antibody employed in the immunoassay. We observed that hypotonic stretch of cultured atrial myocytes induced the release of APir, which was enhanced (10-to 13-fold) when the cells were incubated in calcium-depleted medium containing EGTA or when the cells were pretreated with the intracellular calcium antagonist, 1, 2-bis(2-aminophenoxy)ethane N,N,N',N'-tetraacetic acid (6).…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, the prohormone atriopeptin (AP)-126 [atrial natriuretic factor (ANF)- ] is stored in the atrial granules as the unprocessed prohormone (4). Cultured fetal or neonatal atrial myocytes release intact prohormone into the incubation medium in both the basal state (5) and when stimulated by stretch with hypotonic medium (6). On the other hand, isolated perfused rat or rabbit hearts only release mature hormone, AP-28 [ANF-(99-126)] (7)(8)(9).…”
mentioning
confidence: 99%
“…It has been demonstrated that increased atrial stretch caused by increasing intravascular and atrial volume results in the secretion of ANP in several animal and human models (23,24). Increasing cell volume with hypoosmolar solutions results in cellular distension (stretch) and has recently been shown to increase ANP secretion from isolated atrial and ventricular myocytes (20). Our results indicate that over a wide range of osmolalities, both hypo-and hypertonic to the usual incubation medium, ANP secretion from diencephalic neurons in vitro is unaffected.…”
Section: Discussionmentioning
confidence: 99%